Torta de mamona destoxificada para suínos nas fases de crescimento e terminação - Silva, Taisa Rocha Gomes da (2014)
Two experiments were conducted to evaluate the use of detoxified castor cake pig growing and finishing. In the first experiment 24 male pigs were neutered the same commercial line, with initial weight of 57.84 ± 2.89 kg for the biological evaluation of castor bean under different detoxification processes (CaO, autoclave, CaO + silage, autoclave + silage and extruded), using the method of total collection. The pies were detoxified by the methods using calcium oxide and autoclaved both silage had the lowest values of metabolizable energy, and pies detoxified using CaO + silage and extruded, had lower values of digestible energy. The second assay used 40 barrows, with initial weight of 44.59 ± 5.16 kg, fed diets at levels of 0, 7, 14 and 21% of detoxified castor cake. The animals were slaughtered weighing around 100 kg, being evaluated for performance, the digestive tract organ weights, carcass characteristics and economic evaluation of the use of diets. The inclusion of detoxified castor cake, worsened weight gain and feed conversion. The digestibility of dry matter, crude protein and gross energy were negatively affected by the inclusion of castor cake levels. There were reductions in the yield of loin eye area and ham when the castor cake in the diet was included. The detoxification processes affect the metabolizable energy and protein castor cake for pigs. The inclusion of detoxified castor cake in growing pigs diet and termination worsening weight gain, diet digestibility and yield of the shank. The economic analysis was not efficient use of castor bean cake detoxified with CaO in cost benefit for pigs in growing and finishing.